Finding the drastic : exploring forms of attention in piano performance : a thesis presented in partial fulfillment of the requirements for the degree of Master of Musical Arts in Performance at Massey University, Wellington, New Zealand - Binnie, Michele (Massey University, 2014)
While Carolyn Abbate’s essay “Music – Drastic or Gnostic” sets provocative parameters for considering performance, she also makes a bold stand on the mutual exclusivity of the knowing or gnostic mind and active or drastic body in performance. Abbate suggests that when one is involved in the real-time experience of music (i.e. performance) there is no room for thought because conceptual awareness interrupts the real-time experience. Thus, drastic precludes gnostic. Yet many performers speak about the need to negotiate a balance between mind and body in performance. This implies that an imbalance can occur in either direction, that over-thinking the execution is not conducive to flow but that the ultimate experience of the music ‘playing itself’ may also incur an undesirable sense of not being in conscious control. This paper aims to explore the limits of a gnostic approach and the parameters for a drastic performance. My own experience has demonstrated the ways in which too much conscious control - or rather, too much conscious attention on certain tactile aspects of playing - can end up hampering the physical execution. Indeed, Science Daily has summarised recent research in the Journal of Neuroscience that confirms scientifically that over-thinking can be detrimental to performance. Implicit memory (unconscious and expressed by means other than words) and explicit memory (which is conscious and can be described in words) each operate from different parts of the brain; and the implication is that physical performance in most cases requires the deployment of implicit as well as explicit memory. For a pianist, in other words, on the one hand the ‘action’ must become instinctive at some point because one’s attention cannot focus simultaneously on the fingers prior to every sound and on the sound itself. On the other hand, it is also not desirable simply to deliver the action to some level of drastic, or pure ‘doing’ (as the ancient meaning of the word suggests), even to a meta-drastic point where the music ‘plays itself’. Thus it would seem that Abate’s stipulation gnostic or drastic requires further reflection. Through my critical analysis of this discussion, I would like finally to be able to redress the balance between a gnostic and drastic approach in my own performance. Resituating the mind-body balance itself requires a shift in consciousness: a shift that effectively distracts me from overt tactile awareness and places my foreground attention to sound. This shift, ironically, requires an immense conscious effort: in other words, my shift towards the drastic is launched by the gnostic. Through documenting the process of my own journey from gnostic/explicit performance to drastic/implicit performance, I will propose that a specific balanced blend is ideal: that is, I need to move from a cognitive or conscious process that focuses on physical aspects of performance, in order to bring an unfettered consciousness of sound to the foreground attention. If I can suppress my conscious attention to the kinetics of playing the piano and this very suppression permits a focus on sound itself, will that be a shutting down of one kind of excessive cognitive effort and signal a release of the drastic, or simply resituate the gnostic? For myself, finding my way to trusting a drastic approach and yet balance it with a gnostic input is imperative if I am to find music making a pleasure.
Keywords: Music performance; Piano music performance; Psychological aspects; Mind and body; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Music